Pengaruh Pandemi Covid-19 Terhadap Usaha Mikro Kecil Menengah Ditinjau Dari Sudut Permintaan Pasar Dan Penurunan Daya Beli Di Kota Cirebon - Yolanda Albertina; Sudadi Pranata; Stefanny Christina (Jurnal EBI, 2022)
Micro, Small and Medium Enterprises (MSMEs) is a term in the economic field which refers to productive economic businesses owned by individuals or legal entities that have a net worth of Rp. 200,000,000 and has annual sales of Rp. 1,000,000,000 and stand alone. The purpose of this study was to determine the impact of the Covid-19 pandemic on the Indonesian economy, especially MSMEs themselves. Researchers will conduct research to determine the effect of the Covid-19 pandemic on MSMEs in terms of market demand and the decline in purchasing power in Cirebon City. The results of this study are based on a series of statistical calculations, there are three hypotheses including the first hypothesis. It is known that the significant value is 0.000 0.05 and the t value is 4.688 t table 1.993 so it can be concluded that H1 is accepted. The results of the second hypothesis are known to be significant. of 0.212 0.05 and the value of t count 1.259 t table 1.993 so it can be concluded that H2 is rejected. And finally, the results of the third hypothesis are known to have a significance value of 0.000 0.05 and a calculated F value of 28.505 F table 3.12 so that it can be concluded that H3 is accepted which means that there is a simultaneous effect. Key words: MSME Business, Market Demand, Decline in Purchasing Power